Blitz - O'Malley, Daniel; HarperCollins (Sydney, New South Wales : HarperCollins Publishers, 2022)
From the wild imagination of Daniel O'Malley comes the next thrilling novel set in the world of the bestselling The Rook (now a TV series). After a woman discovers she has supernatural powers, a string of murders is committed by someone using those same powers. As she goes on the run she discovers the roots of the mystery lie in the events of London's Blitz in WW2. Praise for Daniel O'Malley: 'Endlessly imaginative and stupendously diverting' Australian Women's Weekly 'You know you have written a remarkable debut novel when two of the biggest-selling queens of the fantasy genre - Charlaine Harris and Stephenie Meyer - embrace your work.' Courier Mail 'We are clearly in Jasper Fforde, Douglas Adams and Tom Holt territory, but O'Malley is decidedly his own voice. Stiletto is a worthy sequel to The Rook and will be eagerly devoured, a relevant word given the context of the novel, by O'Malley's increasing number of global fans.' Sydney Morning Herald 'I just love this book!' Charlaine Harris on Stiletto 'A bit of Jasper Fforde, a bit of X-Files, and a lot of action' Deborah Harkness.
General.
Keywords: London (England) -- History -- Bombardment, 1940-194.; Comic (humorous) fantasy; Fantasy; Fiction - Fantasy - Contemporary; Fiction & related items; Science fiction; Science fiction: military; Thriller / suspense fiction; Electronic books; Science fiction